The sensitivity of house prices under varying monetary regimes: the Nordic scenario. Issue 1 (6th February 2017) - Cajias, Marcelo; Ertl, Sebastian
Abstract : Purpose: This paper aims to examine whether there are differences between the long and short-term relationship of house prices and interest rates. The elasticity of house prices to monetary policy changes, e.g. via interest rates, is from a theoretical perspective and in the long-run negative. However, house prices adapt in the short-run dynamically to economic, financial, institutional and demographic factors. Design/methodology/approach: In this paper, the authors confirm the aforementioned elasticity for the Nordic housing markets but provide evidence of drastic deviations from the negative relationship. This is done by using rolling regressions in search for time-varying betas. Findings: The empirical results show that recessionary and expansionary policy regimes play a much more important role in the development of house prices in Finland, Sweden and Norway, than in Denmark. Originality/value: Further, it is shown that the relationship between house prices and monetary policy is discontinuous over time, with large deviations from the long-term beta during the past decade. This holds true especially since the beginning of the financial crisis and the expansionary monetary policy in Europe.